A TRIZ-based algorithm for business model innovation in manufacturing SMEs: a systematic framework for strategic innovation integrated with the business model canvas - Juan G. Mejia-Duque; Andres Guerrero-Alvarado (Cogent Business & Management)
In volatile emerging markets, Small and Medium-sized Enterprises (SMEs) face high early-stage failure rates, making long-term sustainability challenging. Many attempt to modify their business models but struggle due to financial constraints, operational inefficiencies, limited-scope approaches, and a lack of structured problem-solving methods. Existing Business Model Innovation (BMI) efforts often lack replicable methodologies and fail to address the limitations of the Business Model Canvas (BMC) in systematic problem-solving. This research proposes a TRIZ-based algorithm integrated with the BMC to overcome these barriers, enhancing SMEs’ sustainability through structured BMI. A single-case study in a Colombian manufacturing SME demonstrated measurable improvements in resource allocation, cost efficiency, quality, customer engagement, and market opportunity identification, strengthening competitiveness and value creation. The algorithm systematically transforms business models by applying TRIZ to all BMC components, addressing SMEs’ key challenges and positioning TRIZ as a strategic BMI tool rather than just a problem-solving method. Key limitations include the resource-intensive nature of BMI, TRIZ’s steep learning curve, and challenges in adapting to dynamic markets. Future research could explore adapting this framework to non-manufacturing sectors and large enterprises. Additionally, the long-term application of this TRIZ-based approach will enhance SMEs’ resilience, ensuring sustained innovation, adaptability, and competitiveness in evolving markets.